R.0.A.R. The Next Normal: Developing Malaysian University Students’ Resilience, Optimism, Adaptability, and Readiness for (Post-)COVID-19 Future of Work Across Professions - Cheong, Huey Fen; Fung, Chorng Yuan; Agnes Lim, Siang Siew
Malaysia has been heavily affected by COVID-19 in various aspects (see the “COVID-19 in Malaysia” book series: Lim, Kaur, & Cheong, 2022; Louis, Kaur, & Cheong, 2022; Pandian, Kaur, & Cheong, 2022). The COVID-19 transition from pandemic to endemic, also from the New Normal to the Next Normal, witnesses a transition of foci from COVID-19 victims and challenges to COVID-19 survivors and R.O.A.R. (Resilience, Optimism, Adaptability, and Readiness/Recovery). R.O.A.R are essential to be resilient. University educators need to equip students with R.O.A.R. to get them READY for the COVID-19-affected future, especially in finding jobs – future career READINESS. Based on career-related courses at a Malaysian university, this paper will illustrate how career reflective assignments can be (re)constructed to develop R.O.A.R among university students as future jobseekers. The reflections cover five aspects: work values, work conditions, transferrable skills, career planning, and career adapt-abilities. This paper also analyses R.O.A.R within students’ career reflections across disciplines, i.e. across industries and professions. It hopes to contribute to the contemporary/(post-)COVID-19 career curricula, teaching, and counselling.